Contemporary Islamic Legal Thought Methodology: A Comparative Study Between Indonesia and Malaysia - Mursyida, Aisyah Nurhalisha (Universitas Islam Negeri Sumatera Utara, 2026)
This article analyzes the methodological development of contemporary Islamic legal thought through a comparative study of Indonesia and Malaysia. Using qualitative library research with a normative-comparative approach, the study examines academic literature, fatwas, and Islamic legal regulations in both countries. The findings reveal that although both Indonesia and Malaysia employ maqāṣid al-syarī‘ah as a primary framework, their orientations differ significantly. Indonesia demonstrates a plural, academic, and contextual approach by integrating classical uṣūl al-fiqh with hermeneutical and socio-historical perspectives. In contrast, Malaysia adopts a more formal-legal orientation, institutionalizing Islamic law through state legislation and Syariah courts. These differences indicate that contemporary Islamic legal methodology is not monolithic but shaped by socio-political structures and national legal systems. The study contributes to the discourse on Islamic legal reform by highlighting the contextual dynamics of methodological development in Muslim-majority countries.